Use of Different Tools in Teaching a Foreign Language in ESP Lessons - Malika Mekhriddinovna Husamiddinova; Xurmatoy Sabirovna Valieva (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information on the specific aspects of teaching a foreign language to students of higher education institutions in ESP classrooms. ESP teachers play an important role in high education.